Prevalence and factors associated with severe anaemia amongst under-five children hospitalized at Bugando Medical Centre, Mwanza, Tanzania. Issue 1 (December 2015) - Simbauranga, Rehema; Kamugisha, Erasmus; Hokororo, Adolfine; Kidenya, Benson; Makani, Julie
Abstract Background Anaemia is a major public health problem in developing countries, contributing significantly to morbidity and mortality amongst children under-five years of age. About 43 % of under-fives are anaemic worldwide, and two-thirds reside in sub-Saharan Africa. Even where blood transfusion is available for treatment there is still a significant case fatality rate ranging between 6 and 18 %. This study aimed to determine the prevalence and morphological types of anaemia, as well as factors associated with severe anaemia in under-five children admitted at Bugando Medical Centre (BMC). Methods This was a hospital-based, cross-sectional study conducted between November 2012 and February 2013. Selected laboratory investigations were done on children admitted to BMC. Anaemia was defined using WHO criteria. Results A total of 448 under-five children were recruited into the study. The overall prevalence of anaemia was 77.2 % (346/448) with mild, moderate and severe anaemia being 16.5, 33 and 27.7 % respectively. Microcytic hypochromic anaemia was detected in 37.5 % of the children with anaemia. Of 239 children with moderate and severe anaemia, 22.6 % (54/239) had iron deficiency anaemia based on serum ferritin level less than12 μg/ml. The factors associated with severe anaemia included unemployment of the parent, malaria parasitaemia and presence of sickle haemoglobin. Conclusion The prevalence of anaemia among under-five children admitted at BMC was high. Iron deficiency anaemia was the most common type. Factors associated with severe anaemia were unemployment among caretakers, malaria parasitaemia and presence of sickle haemoglobin.